Kwintus Sertoriusz a Iberowie - Ładoń, Tomasz (Collectanea Philologica, 2022)
The author of the article deals with three issues. Firstly, he defines the reasons and nature of the changes applied by Sertorius in the treatment of the natives immediately after taking the governorship in Spain. Secondly, he presents Sertorius’ efforts to gain the support of the Iberian elite. Thirdly, he points to the reasons for his support among the broad masses of the Iberians. The author determines that Sertorius’ leading a new, often pioneering, policy towards the Iberian people had one main goal: to provide him with the greatest possible support for the Iberians, which in effect was to lead to mass joining of the natives in the ranks of his army. This policy included granting the natives privileges in the form of exemptions from taxes and from the duty of garrisoning military forces, promoting the Iberian elite and even granting them Roman citizenship. Sertorius did not avoid the use of political propaganda, in which he did not differ from other leaders of his time: Sulla, Pompey and Metellus. These measures ensured him immense popularity. As a result, at the height of the war, tens of thousands of soldiers fought in the Marian ranks and controlled most of the Iberian Peninsula.